Oral multiunit pellet extended release dosage form: A review - Sachdeva, Vishal; Alam, Md. Shoaib; Kumar, Ramesh; Kataria, Mahesh Kumar (International Current Pharmaceutical Journal, 2013)
Oral drug delivery is the most preferred route for the various drug molecules among all other routes of drug delivery, because ease of administration which lead to better patient compliance. So, oral extended release drug delivery system becomes a very promising approach for those drugs that are given orally but having the shorter half-life and high dosing frequency. Recent trends indicate that multiparticulate drug delivery systems are especially suitable for achieving extended release oral formulations with low risk of dose dumping, flexibility of blending to attain different release patterns as well as reproducible and short gastric residence time. The release of drug from pellets depends on a variety of factors including the carrier used to form pellets and the amount of drug contained in them. Consequently, pellets provide tremendous opportunities for designing new controlled and extended release oral formulations, thus extending the frontier of future pharmaceutical development. DOI: http://dx.doi.org/10.3329/icpj.v2i10.16413 International Current Pharmaceutical Journal, September 2013, 2(10): 177-184